Los Usuarios y las Instalaciones Interpretativas del Centro de Visitantes Aguas Calientes — Parque Nacional Puyehue - Oltremari Arregui, Juan (Bosque (Valdivia), 1979)
Th e present study has the purpose of to identify the reaction of visitors to the interpretive facilities of Puyehue Nationa l Par k Visitor Center, to evaluate the understanding and interest of visitors related to interpretive media (exibits) and to identify those, characteristics of users which are important to select future developments. The survey analizes socio demographics characteristics of visitors, lenght of stay at the Visitor Center and at the Park, final destination of the visit, and the composition of social group. It also discuss general reaction to interpretive facilities and the specific interest for certain subjects and designs. Finally it analizes complexity of exhibits and the aspects which must be improved to increase the efectiveness of the interpretive program. Results wer e obtained through a personal interview, random selected, to the users of Puyehue Nationa l Par k Visitor Center (Ho t Springs). Data obtained wer e computed processed under the SPSS program, using chisquare test to identify statistical differences between variables.